AB0823 Patients with connective tissue disease have more anxiety in comparison with patients with other rheumatic diseases. (12th June 2018) - Jiang, Y.; Lin, D.; Zhang, P.; Zhang, X.; Liao, Z.; Pan, Y.; Gu, J.
Abstract : Background: Rheumatic diseases often coexists with psychological disorders. Psychological symptoms not only have a substantial negative impact on the quality of life, but also on the course and outcome of the chronic disorders. 1 Objectives: Our study was to investigate psychological disorders in Chinese patients with rheumatic diseases and to compare the differences of psychological disorders among different diseases. Methods: Patients with rheumatic diseases were enrolled from July to December in 2017 in rheumatology department of the Third Affiliated Hospital of Sun Yat-sen University. Participants were required to complete a set of questionnaires and examinations, including demographic and clinical information, Zung self-rating anxiety scale (SAS), and Zung self-rating depression scale (SDS). The Statistical Package for Social Sciences (SPSS) software version 21 was used for all data management and analysis. The Mann-Whitney U test and Student's t test were used to compare patients with different rheumatic diseases and psychological disorders. Stepwise linear multiple regression was used to determine the contributors to SAS and SDS. Results: Of all the 153 patients, 49 (32%) were male patients. 14.4% had only primary education, while 32% received education in university. Numbers of the patients were stated as follows. Lupus, 44; rheumatoid arthritis, 11; Sjogren's syndrome, 11; systemic sclerosis, 9; myositis, 7; vasculitis, 6; spondyloarthritis, 9; gout, 10; other diseases 46. Mean age was 37.64±15.23 years. Mean disease duration was 3.78±5.07 years. Mean SAS scores were 43.44±8.51, and mean SDS scores were 46.66±12.43. 35 (22%) of the patients had anxiety, while 6 (3.9%) had moderate anxiety. 50 (32.7%) patients suffered from depression, of which 5 (3.3%) had severe depression, and 13 (8.5%) had moderate depression. Patients with connective tissue diseases had more anxiety (30.5%) than average score (p<0.05), especially in patients with lupus. SDS (B=1.073, p<0.001), educational scale (B=−2.147, p<0.05) contributed to SAS scores. Conclusions: Psychological disorders could concur with rheumatic diseases, especially in connective tissue diseases. Physicians should be aware of psychological status in these patients. Reference: [1] Gladis MM, Gosch EA, Dishuk NM, Crits-Christoph P (1999) Quality of life: expanding the scope of clinical significance. J Consult Clin Psychol67:320–331. Acknowledgements: None. Disclosure of Interest: Y. Jiang: None declared, D. Lin: None declared, P. Zhang: None declared, X. Zhang: None declared, Z. Liao Grant/research support from: National Natural Sciences Foundation of China [grant number 81201372], Y. Pan: None declared, J. Gu Grant/research support from: the 5010 Subject of Sun Yat-sen University (2007023)